SIAPAKAH PENCIPTA SESUNGGUHNYA DARI SEBUAH FILM LAYAR LEBAR ‘LASKAR PELANGI’? - Larasati Endah Purnamasari (Program Magister Ilmu Hukum Universitas Pancasila, 2022)
Throughout the history of the Indonesian film industry, the most frequent type of film adaptation produced has been film adaptations of novels. This is because there has always been a great public interest to experience an existing story or narrative in different media or formats. This is so for the adaptation of the novel ‘Laskar Pelangi ‘ with a film of the same title ‘Laskar Pelangi ‘. Then arises the question of who is the creator of a movie from the adaptation of the novel? To answer this question, a deep analysis was conducted on the scope of Intellectual Property Rights, specifically Copyright, for the film ‘Laskar Pelangi’. The juridical normative approach was used with the character perspective specification as it aims to obtain suggestions that could be used to solve a problem. Based on our analysis, an author is entitled to the ownership of their work for the transformation of a story from a novel into another form of media, such as film. The film itself would include the dramatization of the novel and include material changes and arrangements that would generate a new version of the narrative. A writer, as a creator, has been given ownership rights directly by Law of the Republic of Indonesia Number 28 of 2014 on Copyright. This suggests that the writer of the novel ‘Laskar Pelangi ‘ as well as its adaptations, Andrea Hirata, can enjoy the results of his work by transferring his economic rights and has the right to create any form of adaptation from his novel. Thus, Andrea Hirata as the writer of the novel ‘Laskar Pelangi’ is the creator of every form of adaptation of his novel, regardless of the parties that create these adaptations. Therefore, Andrea Hirata is the creator of the film ‘Laskar Pelangi ‘ while the director (Riri Riza) and Miles Film & Mizan Production are the Copyright Recipients who would receive the economic rights from the movie ‘Laskar Pelangi’ as given by Andrea Hirata